Unfastened : Globality and Asian North American Narratives - Ty, Eleanor Rose, 1958- (Book collections on Project MUSE., 2010)
Unfastened examines literary works and films by Asian Americans and Asian Canadians that respond critically to globality--the condition in which traditional national, cultural, geographical, and economic boundaries have been--supposedly--surmounted. In this wide-ranging exploration, Eleanor Ty reveals how novelists such as Brian Ascalon Roley, Han Ong, Lydia Kwa, and Nora Okja Keller interrogate the theoretical freedom that globalization promises in their depiction of the underworld of crime and prostitution. She looks at the social critiques created by playwrights Betty Quan and Sunil Kuruvilla.